Ancestral and Subsistence Food: Discourse and Control of Maize Cultivation and Consumption in Mexico, 1937-1961 - Pedroza Ortega, Luis Ozmar (Universidad Pedagógica y Tecnológica de Colombia, 2023)
The aim of this article is to analyse how, during the period of 1937 to 1961, different Mexican governments used the cultural and ancestral dimension of maize, overcoming the controversiesaround its nutritional quality and utilising the benefits of agricultural research, to incentivise its production and consumption among the population, as well as its exportation to other countries, with the goal of turning it into a commodity that would incorporate the rural population into the national economy. For this reason, it was important to design campaigns to promote this grain in various media, seeking to exalt the idea of the ancestral food that was the basis of the Mexican diet and a symbol of Mexican culture. This analysis was constructed using contemporary newspapers and other publications of the period mentioned, as well as works that have addressed the topic of maize cultivation and consumption. The article seeks to deepen our understanding of the changes in the Mexican diet, the practices of production, and the sociocultural significance of maize as from the mid-twentieth century.